Problematika Guru Dalam Menulis Karya Ilmiah SebagaiPengembangan Kompetensi ProfesionalDi Sd Muhammadiyah 5 Surakarta - Danawati. M, Ismi; , Dra. Risminawati, M.Pd (2017)
One figure that plays an important role in education is the teacher. The teacher's role is crucial to success in the educational process. Writing scientific papers for teachers to have such great benefits,among others, can enhance the learning competencies in students, and can also be trained to be morecreative and innovative in implementing learning. This study aimed to describe: (1) the ability of theteacher in writing scientific papers as a form of development of professional competence; (2)teachers' understanding of the development of professional competence; (3) the constraints ofteachers in writing scientific papers as the development of professional competence; (4) Principalefforts in ddressing the issue of teachers the ability to write scientific papers as the development ofprofessional competence in SD Muhammadiyah 5 Surakarta. This research is qualitative research.The study design used is descriptive. Data collection techniques used were interviews, observation and documentation. The validity of research data using triangulation source and technique. Theanalysis technique used is the analysis of qualitative data. Based on the results, this study shows that :(1) The ability of the teacher in writing scientific papers are considered able to prove to have writtena scientific paper with the type of PTK; (2) Understanding on the development of professional competence of teachers still look less; (3) Barriers teacher in writing scientific papers as thedevelopment of ofessional competence in SD Muhammadiyah Surakarta 5, the first is to timeconstraints, lack of motivation, lack of understanding of professional competence, the limitations ofdeveloping ideas in writing scientific papers; (4) the efforts taken by the Principal among others:Includes teachers into ialization, seminars, and workshops related to writing scientific papers;Involving teachers in training that was held outside the school; Involving teachers in discussions related to writing scientific papers in KKG; Allowing teachers the opportunity to participate in thecompetition with regard to writing ,; Adding supporting books in the library